Pengaruh Kompetensi Dan Disiplin Kerja Terhadap Kinerja Pegawai Di Dinas Pekerjaan Umum Dan Penataan Ruang Kabupaten Karawang - Irtawan, Luvita; Ramdani, Dany (Peneliti.net, 2024)
Luvita Irtawan, 2024. The Influence of Competency and Work Discipline on the Performance of District Public Work and Spatial Planning Employees. Karawang. Thesis Bachelor of Management Program, Faculty of Ecomicics and Business, Singaperbangsa University, Karawang. This research aims to examine and analyze the influence of work competency and discipline on the performance of Karawang Regency publicworks and spatial planning (DPUPR) employees. This research was carried out using quantitative menthods with drescriptive and verificative analysis, namely collecting, presenting analyzing and testing hypotheses, as well as making conclusions and suggestions. The sample in this study consisted of 110 respondents and used a non-probability sampling technique. Namely saturated or sensu sampling. The data analysis techniques used are likert scale analysis techniques and path analysis. Based on the analysis that has been carried out, this research proves that the correlation between the competence and work discipline variables has obtained a value of 0,270, Which meand the relationship between variables, The partial influence of competency on performance is 0,692 or 69,2%. The partial effect of work discipline on performance is 0,098 or 9,8%, so it can be stated that competence has a greater influence on performance compared to work discipline. The simultaneous influence of competency and work discipline on performance is 0,451 or 45,1%, while the remaining 0,54 or 54% is the influence or other variables that were not examined.